재활 낮병동 프로그램이 뇌성마비아동의 대동작기능에 미치는 효과 - 김기전(Ki-Jeon Kim) (한국콘텐츠학회 논문지, 14(5), 2014)
The purpose of this study was to find the effect of Day Hospital Rehabilitation programs on gross motor function in children with cerebral palsy. The subjects were 57 children with spastic cerebral palsy with no previous botulinum toxin injection or operation history within 6 months. The Gross Motor Function Measure(GMFM) score and Gross Motor Function Classification System(GMFCS) were used to evaluate as functional change and functional level. The Programs for Day Hospital Rehabilitation period for cerebral palsy children was 8 weeks. The results of the study are as follows: 1, GMFM Score of pre- and post-programs for Day Hospital Rehabilitation showed the statistically significant difference(p <.001). 2, The age group in 1-2 was higher than age 5-6 group, 3-4 was higher than age 5-6 group by Post-hoc analysis. Lastly, there was significantly different of GMFM in GMFCS level(p<.05), especially mild(GMFCS level I) and moderate(GMFCS level II, III) of CP showed that gross motor function was significantly different than severe(GMFCS level IV, V). The programs for Day Hospital Rehabilitation was effective on gross motor function for children with cerebral palsy, and for early intervention needs to mild, moderate CP, and below age 4 group. 본 연구에서는 뇌성마비아동의 대동작기능이 재활 낮병동 프로그램을 통한 효과를 알아보고자 실시하였다. 연구대상자는 경직성 뇌성마비아동 57명으로 최근 6개월 사이에 보톨리눔 독소나 수술적 병력이 없는 아동을 대상으로 하였다. 대동작기능 측정(GMFM)와 대동작기능 분류체계(GMFCS)를 기능적 변화와 기능적 수순에 대한 평가를 실시하였으며, 낮병동 프로그램은 8주로 이루어졌다. 연구결과는 다음과 같다. 첫째, 낮병동 프로그램 적용을 통한 치료 전 후 대동작기능의 유의한 차이를 보였다(p<.001). 둘째, 연령별 운동발달은 1-2세, 3-4세 뇌성마비아동이 5-6세 뇌성마비아동보다 사후검정 결과 더 높은 것으로 나타났다. 마지막으로, 대동작기능 분류체계(GMFCS) 수준l에 따른 대동작기능 측정(GMFM)의 유의한 차이를 보였는데(p<.05), 특히 경도와 중등도 뇌성마비아동이 중증도 뇌성마비아동보다 유의한 차이를 보였다. 낮병동 프로그램은 뇌성마비아동의 대동작기능의 운동발달에 효과적이며, 경도, 중등도와 4세 이하의 뇌성마비아동에게 조기 중재가 필요할 것으로 생각된다.